Stereoselectivity in Autoionization Reactions of Hydrogenated Molecules by Metastable Noble Gas Atoms: The Role of Electronic Couplings. Issue 35 (29th July 2016) - Falcinelli, Stefano; Rosi, Marzio; Cavalli, Simonetta; Pirani, Fernando; Vecchiocattivi, Franco
Abstract: Focus in the present paper is on the analysis of total and partial ionization cross sections, measured in absolute value as a function of the collision energy, representative of the probability of ionic product formation in selected electronic states in Ne*−H2 O, H2 S, and NH3 collisions. In order to characterize the imaginary part of the optical potential, related to electronic couplings, we generalize a methodology to obtain direct information on the opacity function of these reactions. Such a methodology has been recently exploited to test the real part of the optical potential (S. Falcinelli et al., Chem. Eur. J ., 2016, 22, 764–771). Depending on the balance of noncovalent contributions, the real part controls the approach of neutral reactants, the removal of ionic products, and the structure of the transition state. Strength, range, and stereoselectivity of electronic couplings, triggering these and many other reactions, are directly obtained from the present investigation. Abstract : Beyond imagination : Analysis of total and partial ionization cross sections representative of the probability of ionic product formation in selected electronic states in Ne*‐H2 O, H2 S, and NH3 collisions has been studied. In order to characterize the imaginary part of the optical potential, related to electronic couplings, a methodology to obtain direct information on the opacity function of these reactions has been generalized (see figure).